The yellow elephant improve your memory to learn more, faster, better - Ali, Tansel (Hardie Grant Books, 2013)
The author, an Australian Memory Champion shows how four simple but powerful memory techniques can be learnt to train your brain for better recall and applied for success in education and study, business, performance and the arts and general brain health